2020
DOI: 10.3389/fpls.2020.576378
|View full text |Cite
|
Sign up to set email alerts
|

MiR858b Inhibits Proanthocyanidin Accumulation by the Repression of DkMYB19 and DkMYB20 in Persimmon

Abstract: Persimmon proanthocyanidin (PA) biosynthesis is controlled by structural genes and regulated by transcription factors (TFs). MicroRNAs are a key factor involved in regulating gene expression at the posttranscriptional level whose functions in persimmon PA biosynthesis are poorly understood. Here, we identified a microRNA, miR858b, that putatively targets two R2R3-MYB TFs, DkMYB19 and DkMYB20. DkMYB19, DkMYB20, and miR858b showed divergent expression patterns during fruit development, and the interaction betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In grapes, the activation of miR858 led to a significant downregulation of its target gene VvMYB114 , a repressor of anthocyanin, thereby inducing excessive anthocyanins accumulation . In contrast, the reduced expression of miR858 using the STTM strategy improved the accumulation of anthocyanin by targeting SlMYB48-like , MdMYB9 , and MdMYBPA1 transcripts in tomatoes and apple calli. , In addition, DkMYB20 was conducive to regulating the biosynthesis of PAs, whereas miR858b directly repressed the transcription of DkMYB20 , which contributed to the accurate regulation of PA accumulation in persimmons . In apple calli, miR858 induced the accumulation of PAs by downregulating the expression of the three transcription factors MdMYB9 , MdMYB11 , and MdMYB12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In grapes, the activation of miR858 led to a significant downregulation of its target gene VvMYB114 , a repressor of anthocyanin, thereby inducing excessive anthocyanins accumulation . In contrast, the reduced expression of miR858 using the STTM strategy improved the accumulation of anthocyanin by targeting SlMYB48-like , MdMYB9 , and MdMYBPA1 transcripts in tomatoes and apple calli. , In addition, DkMYB20 was conducive to regulating the biosynthesis of PAs, whereas miR858b directly repressed the transcription of DkMYB20 , which contributed to the accurate regulation of PA accumulation in persimmons . In apple calli, miR858 induced the accumulation of PAs by downregulating the expression of the three transcription factors MdMYB9 , MdMYB11 , and MdMYB12 .…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic tree analysis indicated that GhTT2L clustered into the PA-related MYB clade and was closer in systemic evolution to AtTT2, DkMYB2, and VvMYBPA2 (Figures 1B, S2, and Table S2), which were previously described as biosynthetic regulators of PAs. 6,10 Furthermore, GhTT2L-pGBKT7-positive yeast cells grew normally on yeast amino acid deficient medium, indicating that GhTT2L possessed transcriptional activation activities (Figure 1C). Interestingly, the expression pattern of GhTT2L was contrary to that of GhmiR858 and significantly decreased in HS2 (Figure 1D).…”
Section: Ghmir858 Is Highly Expressed In a G Hirsutummentioning
confidence: 96%
See 1 more Smart Citation
“…The empty vector pGreenII 62-SK was used as a negative control effector. Transformation and infiltration were performed as described in Yang et al [ 48 ]. The luciferase signals were observed by an imaging apparatus (Plant View 100, Guangzhou, China).…”
Section: Methodsmentioning
confidence: 99%
“…All these reactions might point to stress prevention role, possibly against reactive oxygen species (ROS), which are frequently produced during plant stress responses. The DkMYB 2 CT controller reacts to injury in Diospyros kaki , together with the CT biosynthetic genes, indicating that D. kaki CTs could be inducible ( Yang et al., 2020 ).…”
Section: Tanninsmentioning
confidence: 99%